2010
DOI: 10.1242/dmm.005058
|View full text |Cite
|
Sign up to set email alerts
|

UDP-galactose 4′ epimerase (GALE) is essential for development ofDrosophila melanogaster

Abstract: SUMMARYUDP-galactose 4' epimerase (GALE) catalyzes the interconversion of UDP-galactose and UDP-glucose in the final step of the Leloir pathway; human GALE (hGALE) also interconverts UDP-N-acetylgalactosamine and UDP-N-acetylglucosamine. GALE therefore plays key roles in the metabolism of dietary galactose, in the production of endogenous galactose, and in maintaining the ratios of key substrates for glycoprotein and glycolipid biosynthesis. Partial impairment of hGALE results in the potentially lethal disorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(65 citation statements)
references
References 41 publications
4
61
0
Order By: Relevance
“…Whereas loss-of-function mutations in GalT or GalK, the other two genes of the Leloir pathway, have been described (23,24), no cases of functional GalE-null mutants have been reported (25). Consistent with the essential nature of this enzyme, the GalE-deficient fruit fly is developmentally lethal (26). Our data show that GalE knockdown leads to impaired insulin signaling and protein biosynthesis in hepatocytes, implying a potential mechanism for the essential role of GalE in cell survival.…”
Section: Figurementioning
confidence: 99%
“…Whereas loss-of-function mutations in GalT or GalK, the other two genes of the Leloir pathway, have been described (23,24), no cases of functional GalE-null mutants have been reported (25). Consistent with the essential nature of this enzyme, the GalE-deficient fruit fly is developmentally lethal (26). Our data show that GalE knockdown leads to impaired insulin signaling and protein biosynthesis in hepatocytes, implying a potential mechanism for the essential role of GalE in cell survival.…”
Section: Figurementioning
confidence: 99%
“…Reactive oxygen species are also implicated in the formation of galactosemic cataracts (Mulhern et al , 2006;Mulhern et al , 2007;Abdul Nasir et al , 2014). D. melanogaster and Caenorhabditis elegans models of type III galactosemia have also been developed (Sanders et al , 2010;Brokate-Llanos et al , 2014). The fruit fly model demonstrated that GALE is essential for development of the organism (Sanders et al , 2010).…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…D. melanogaster and Caenorhabditis elegans models of type III galactosemia have also been developed (Sanders et al , 2010;Brokate-Llanos et al , 2014). The fruit fly model demonstrated that GALE is essential for development of the organism (Sanders et al , 2010). It also demonstrated that the two physiologically important activities of GALE (epimerisation of UDP-galactose and UDP-N-acetylgalactosamine) were vital and played different roles in development (Daenzer et al , 2012).…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…Some variant GALE proteins are catalytically impaired, while others demonstrate compromised stability, at least under defined laboratory conditions. While the relationship between GALE activity and galactose-sensitivity has been defined in yeast and Drosophila models (Sanders et al 2010;Wasilenko and Fridovich-Keil 2006), the relationship between GALE activity level and outcome severity in patients remains a point of speculation.…”
Section: Introductionmentioning
confidence: 99%